Indonesian Learning Culture Based On Android - Ribka Kowi; Tri Wahyu Widyanigsih (Universitas Multimedia Nusantara, 2017)
Indonesia is the fourth country with the largest population in the world and rich of cultural heritage and local wisdom. However, the majority of Indonesian people are less caring, less knowing and minimum understanding about Indonesian culture because of the lack of facilities to provide information of Indonesian culture. On the other hand, Android development is increasingly rapid and free to develop. This is an opportunity that can be used to build a culture of learning systems to maintain the existence Indonesia culture in the eyes of Indonesian people. This research aims to create a system of Indonesian Culture Learning android based mobile application that can be used as a medium of learning Indonesian culture. The methodology of this development is using SDLC which starting from planning, requirements analysis, system design, implementation, testing and maintenance. And using Android Studio as the main program, Photoshop and Microsoft Paint for image processing, and DIA to design UML. Indonesian Learning Culture can display ten kinds of culture, that is: traditional house, traditional food, traditional clothes, traditional dance, traditional language, traditional music instruments, traditional song, tribe, handy craft and tourist attraction. Where each category shows an example of each of the provinces in Indonesia. Keyword— Android, Indonesian Culture, Mobile Application, SDLC. REFERENCES [1] Alwan, Motea. (2015), what is system development life cycle, retrieved 19 September 2016, <https://airbrake.io/blog/insight/what-is-system-developmentlife-cycle >.J. Clerk Maxwell, A Treatise on Electricity and Magnetism, 3rd ed., vol. 2. Oxford: Clarendon, 1892, hal.68- 73. [2] Arif, Akbarul Huda. 24 JAM!! Pintar Pemrograman ANDROID, Ebook Version 2.1 [3] Arismadhani, A., Yuhana, U.L., Kuswardayan,I. (2013), Aplikasi Belajar Menulis Aksara Jawa Menggunakan Android, JURNAL TEKNIK POMITS, Vol. 2, No.2, retrieved 2 March 2016, <http://download.portalgaruda.org/article.php?article=88965 &val=4186>. [4] DU (n.d) What is Microsoft Paint. [Online] Digital Unite. retrieved 14 November 2016, <https://www.digitalunite.com/guides/microsoftprograms/what-microsoft-paint>. [5] Elmasri, R., and Navathe, Shamkant B. (2011), Fundamentals of Database System Sixth Edition. Pearson Education,Inc. [6] H., Nazruddin Safaat. (2012), Pemrograman Aplikasi Mobile Smartphone Dan Tablet PC Berbasis Android. Bandung: Informatika, pp. 1, 7-8 [7] Haughn, Matthew. (2015), Definition of Photoshop, retrieved 14 November 2016, <http://whatis.techtarget.com/definition/Photoshop >. [8] IBM (n.d) An introduction to the Unified Modeling Language. [Online] IBM. Retrieved 14 November 2016,<http://www.ibm.com/developerworks/rational/library/7 69.html>. [9] Imam, Dyina S., and Sismoro, Heri. (2015), Rancang Bangun Aplikasi Mobile Sebagai Media Pelestarian Lagu Traditional Dan Nasional Indonesia Berbasis Android, Jurnal Ilmiah DASI, Vol.16, No.1, retrieved 2 March 2016, <https://www.google.co.id/url?sa=t&rct=j&q=&esrc=s&sour ce=web&cd=1&cad=rja&uact=8&ved=0ahUKEwjYpozc_97 QAhULLY8KHcbZArcQFggZMAA&url=http%3A%2F%2F ojs.amikom.ac.id%2Findex.php%2Fdasi%2Farticle%2Fview File%2F228%2F213&usg=AFQjCNFbyMXtRJIXS6aIOGaA H7OsViOmxQ&bvm=bv.139782543,d.c2I>. [10] KKBI (n.d) Budaya. [Online] KKBI. Retrieved 14 November 2016, <http://kbbi.web.id/budaya>. [11] McCann, William Jon. (2013), Dia Diagram, retrieved 14 November 2016, <https://wiki.gnome.org/action/show/Apps/Dia?action=show &redirect=Dia>. Murtiwiyati and Lauren, Glen. (2013), Rancang Bangun Aplikasi Pembelajaran Budaya Indonesia Untuk Anak Sekolah Dasar Berbasis Android, Jurnal Ilmiah KOMPUTASI, Vol. 12, No. 2, retrieved 2 March 2016, <https://www.google.co.id/url?sa=t&rct=j&q=&esrc=s&sour ce=web&cd=1&cad=rja&uact=8&ved=0ahUKEwi6oIu_9N7 QAhWMK48KHVJmAncQFggZMAA&url=http%3A%2F% 2Fmurtiwiyati.staff.gunadarma.ac.id%2FPublications%2Ffile s%2F2058%2Fjurnal%2BAndroid.pdf&usg=AFQjCNGipYb EnfrdkyL6XMXnI88vw0Yfnw&bvm=bv.139782543,d.c2I>. [12] Nisafani, Amna N., Muqtadiroh, Feby A., Nugraha, Nanda F. (2014), Analisis Dan Perancangan Wiki Budaya Dalam Rangka Melestarikan Budaya Bangsa Dan Kearifan Lokal Nusantara. SISFO-Jurnal Sistem Informasi, retrieved 2 March 2016, <https://www.researchgate.net/publication/280822614 >. [13] Nugraha, T. S., and Tresnawati, Dewi. (2015), Pengembangan Aplikasi Pengenalan Kesenian Daerah Indonesia Sebagai Media Pembelajaran Berbasis Android. Jurnal Algoritma, Vol. 16, No.1, retrieved 2 March 2016, <http://jurnal.sttgarut.ac.id/index.php/algoritma/article/viewFi le/173/160 >. [14] Rizky, R. and Wibisono, T. (2015), Mengenal Seni & Budaya 34 Provinsi di Indonesia. Jakarta Timur: Cerdas Interaktif. [15] Sembiring, Rehulina. (2014), Panduan Android Studio, retrieved 19 September 2016, <http://panduanandroidstudio.blogspot.co.id/>. [16] Suryana. (2010), Metode Penelitian (Model Prakatis Penelitian Kuantitatif dan Kualitatif). Universitas Pendidikan Indonesia, retrieved 17 October 2016, <http://file.upi.edu/Direktori/FPEB/PRODI._MANAJEMEN_ FPEB/196006021986011-SURYANA/FILE__7.pdf >. [17] UML (n.d) The Unified Modeling Language. [Online] UML. Retrieved 14 November 2016, <http://www.umldiagrams.org/>. [18] Valacich, Joseph S., George, Joey F., and Hoffer, Jeffrey A. (2012), Essentials of System Analysis & Design, 6th edn, Pearson Education,Inc. [19] Wijaya, Raden. (2015), Skala Likert (Metode Perhitungan, Persentase dan Interval, retrieved 14 November 2016, <http://dokumen.tips/documents/skala-likert-metodeperhitungan-persentase-dan-interval.html#>